8 keys to eliminating passive-aggressiveness - Brandt, Anea (Your Coach Digital, 2013)
Guidance for dealing with this common and frustrating form of behavior. Many people often say "yes" to something when they'd rather say "no." They offer cooperation through words but follow up with how they really feel-in actions that contradict their words. That's passive-aggression. At its heart, passive-aggression is about being untrue to oneself, which makes it impossible to have a clean relationship with others. Passive-aggression as a communication method doesn't make someone "bad." It is simply a strategy learned in childhood as a coping mechanism, a hard-to-break habit. Changing passive-aggressive behavior requires knowledge, tools, and practice, as outlined here. This audiobook offers effective methods for transforming passive-aggression into healthy assertiveness to communicate in constructive ways through eight keys: Recognize Your Hidden Anger; Reconnect Your Emotions to Your Thoughts; Listen to Your Body; Set Healthy Boundaries; Communicate Assertively; Interact Using Mindfulness; Disable the Enabler; and Problem-Solve for Better Outcomes. Hands-on exercises are featured, enabling listeners to better understand themselves.
Unabridged
Keywords: Passive-aggressive personality; Anger; Interpersonal communication; Passive-Aggressive Personality Disorder; Personnalité passive-agressive; Colère; Communication interpersonnelle; anger; Downloadable audio books